Na białym szlaku. Zapomniany film o wojnie - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Hendrykowski Marek, Na białym szlaku. Zapomniany film o wojnie [“On the White Trails”: a forgotten film about the war]. „Images” vol. XXVI, no 35. Poznań 2019. Adam Mickiewicz University Press. Pp. 103–115. ISSN 1731-450X. DOI 10.14746/i.2019.35.05. The article is an analytical and interpretative study of behind-the-scenes aspects and the poetics of a little-known feature film titled On the White Trails, directed by Jarosław Brzozowski and Andrzej Wróbel.